The role of Google Scholar Alerts (GSA) in scientific communication: is there any correlation to altmetric indicators? - Sygocki, Witold; Rychlik, Małgorzata (My University, 2018)
The aim of this study was to examine whether Google Scholar Alerts (GSA) have a significance for scientific communication. The study was divided into two stages. The first stage was to collect GSA records representing OSH discipline (N=400). GSA were related to articles published in two journals: International Journal of Occupational Safety and Ergonomics and Applied Ergonomics which are indexed eg. in Scopus. All articles had DOI assigned. The chronological scope of the study covered December 2016 and 2017. The second stage involved the use of the Altmetric Explorer (http://www.altmeric.com) to check whether the journals having more GSA had more altmetric indicators and whether Twitter mentions and Mendeley readers correlated with GSA. Based on the obtained data, the authors will try to answer the following questions: RQ1. Which journal has more GSA? RQ2. How many GSA are non-active? RQ3. Does a journal having more GSA have more altmetric indicators? RQ4. Does the number of GSA assigned to a particular article correlate with the number of altmetric indicators? RQ5. What, if any, is a significance of GSA in scientific communication?
Poster presented at Nordic Workshop on Bibliometrics and Research Policy, Borås, Sweden, 7-9 November 2018
Keywords: Google Scholar Alerts; altmetrics; occupational safety and health; Altmetric explorer